Electronic and Optical Properties of Small Hydrogenated Silicon Quantum Dots Using Time-Dependent Density Functional Theory - Muhammad Mus-'ab Anas Bin Mohd Anas; Geri Gopir (Hindawi Publishing Corporation, 2024)
This paper presents a systematic study of the absorption spectrum of various sizes of small hydrogenated silicon quantum dots of quasi-spherical symmetry using the time-dependent density functional theory (TDDFT). In this study, real-time and real-space implementation of TDDFT involving full propagation of the time-dependent Kohn-Sham equations were used. The experimental results for SiH4 and Si5H12 showed good agreement with other earlier calculations and experimental data. Then these calculations were extended to study larger hydrogenated silicon quantum dots with diameter up to 1.6?nm. It was found that, for small quantum dots, the absorption spectrum is atomic-like while, for relatively larger (1.6?nm) structure, it shows bulk-like behavior with continuous plateau with noticeable peak. This paper also studied the absorption coefficient of silicon quantum dots as a function of their size. Precisely, the dependence of dot size on the absorption threshold is elucidated. It was found that the silicon quantum dots exhibit direct transition of electron from HOMO to LUMO states; hence this theoretical contribution can be very valuable in discerning the microscopic processes for the future realization of optoelectronic devices.